Fiz Pol 2023
DOI: 10.56984/8zg0dfb15
|View full text |Cite
|
Sign up to set email alerts
|

The differences frequency of weekly physical exercise in antioxidant serum levels and muscle damage

Abstract: Problems and Purpose. A measurable physical exercise that follows the rules can improve physiological abilities. However, physical exercise that is not according to the rules, such as lack of recovery time caused by too frequent exercise, can increase the accumulation of free radicals in the body. In addition, the limited recovery time can also increase tissue damage to the muscles. Therefore, this study aims to determine the effect of differences in the frequency of physical exercise in one week on serum anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Muscle hypertrophy and resistance training have been linked. Two main ideas in consistent resistance training are progressive overload and variation to promote continued muscle adaptation (Dewangga & Irianto, 2023). Variability in resistance training refers to the methodical modification of one or more program elements, like volume and intensity, while progressive overload refers to a steady increase in the body's stress (Dewangga et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle hypertrophy and resistance training have been linked. Two main ideas in consistent resistance training are progressive overload and variation to promote continued muscle adaptation (Dewangga & Irianto, 2023). Variability in resistance training refers to the methodical modification of one or more program elements, like volume and intensity, while progressive overload refers to a steady increase in the body's stress (Dewangga et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to do Resistance training at least two or three times a week (Fariz & Dewangga, 2020). Training must be intensified gradually to increase muscle strength by increasing the load or number of repetitions (Dewangga & Irianto, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Their study, which divided the rats into four groups subjected to different exercise frequencies, found that exercising four times a week or daily without sufficient recovery decreased the serum antioxidant levels and increased muscle tissue damage. This underscores the importance of integrating adequate rest days into exercise routines to preserve the body's antioxidant capacity and muscle health [44].…”
Section: Adequate Recovery Periodsmentioning
confidence: 99%
“…Conversely, high-intensity exercise can lead to an overload of reactive oxygen and nitrogen species, overwhelming the antioxidant defense and resulting in cellular damage, muscle fatigue, and impaired recovery, conditions often exacerbated during continuous intense training without adequate rest [26,40,66]. Such scenarios are associated with overtraining syndrome in athletes, characterized by persistent fatigue and reduced performance [29,33,44,46]. Thus, it is critical to design training programs that include proper recovery and nutritional support to moderate the physiological impacts of exercise [34,40,50].…”
Section: Modulation Of Oxidative Stress Through Exercise Intensitymentioning
confidence: 99%
“…Findings revealed that exercising four times a week or daily, without sufficient recovery, led to lower serum antioxidant levels and more significant muscle tissue damage. This highlights the importance of including enough rest days in exercise regimes to prevent adverse effects on the body's antioxidant capacity and muscle health [50]. Implementing active recovery techniques and getting enough sleep can significantly enhance recovery and boost antioxidant defenses, helping to offset exercise-induced oxidative stress.…”
Section: Adequate Recovery Periodsmentioning
confidence: 99%